Model-based testing for smart contracts - Ng, Erica Xiang Qing (Nanyang Technological University, 2023)
At this rate of adoption, blockchain has the potential to revolutionize and reshape the way we live and work. Still, security is an utmost concern. Although researchers have developed tools to analyze the security vulnerability of smart contracts, its behavior remains an area less explored. ModCon is designed to support testing for smart contract’s behavior. This study gives a comprehensive review on the efficiency of ModCon – a model-based testing tool – based on its coverage and its robustness. The coverage of ModCon is evaluated by testing game smart contracts and auction smart contracts on the Ethereum blockchain network. The robustness of ModCon is assessed based on various aspects, such as consistency and reproducibility, by testing the same smart contract on both the Ethereum and FISCO BCOS blockchain networks. ModCon is shown to be not efficient for its coverage for game smart contracts but efficient for auction smart contracts. For robustness, ModCon is not efficient based on reproducibility but efficient based on consistency. In summary, this report documents the testing process which comprises of how states are introduced to smart contracts, the challenges faced, solutions implemented, analysis of the findings and recommendations for the future.